Conflict of interest and medical innovation : ensuring integrity while facilitating innovation in medical research : workshop summary - Beachy, Sarah H.; Berger, Adam C.; Olson, Steve, 1956- (National Academies Press, 2014)
Scientific advances such as the sequencing of the human genome have created great promise for improving human health by providing a greater understanding of disease biology and enabling the development of new drugs, diagnostics, and preventive services. However, the translation of research advances into clinical applications has so far been slower than anticipated. This is due in part to the complexity of the underlying biology as well as the cost and time it takes to develop a product. Pharmaceutical companies are adapting their business models to this new reality for product development by placing increasing emphasis on leveraging alliances, joint development efforts, early-phase research partnerships, and public-private partnerships. These collaborative efforts make it possible to identify new drug targets, enhance the understanding of the underlying basis of disease, discover novel indications for the use of already approved products, and develop biomarkers for disease outcomes or directed drug use. While the potential benefits of collaboration are significant, the fact that the relationships among development partners are often financial means that it is vital to ensure trust by identifying, disclosing, and managing any potential sources of conflict that could create bias in the research being performed together. Conflict of Interest and Medical Innovation is the summary of a workshop convened by the Institute of Medicine Roundtable on Translating Genomic-Based Research for Health in June 2013 to explore the appropriate balance between identifying and managing conflicts of interest and advancing medical innovation. A wide range of stakeholders, including government officials, pharmaceutical company representatives, academic administrators and researchers, health care providers, medical ethicists, patient advocates, and consumers, were invited to present their perspectives and participate in discussions during the workshop. This report focuses on current conflict of interest policies and their effect on medical innovation in an effort to identify best practices and potential solutions for facilitating innovation while still ensuring scientific integrity and public trust.